Enunciação e sintaxe: Modos de enunciação genéricos na ocupação do lugar de objeto - Luciani Dalmaschio (2008)
This work is based on the studies developed by Enunciation Semantics which theorical basis states that the linguistic functioning is constituted by organic and enunciative dimension. In this approach, the focus of the analysis is on the syntactic place verbal object, projected by the verb, but not fulfilled within the sentence. This work, based on this grammatical topic and also in a diverse corpus, works with the proposition that the syntactic silence presents itself as a meaningful constitutive element, as well as occupation conditions are determined by general an specific enunciative forms. This study also discusses that verbal predications are divided both in oriented predications, which occurs when they are guided to an object, and centered predications, which are accomplished when the direction of meaning is guided to the verb. Besides this, this study proposes a categorization of predications centered in: low, medium and high levels. As to, this research is based on an amplitude of referential dominium that is established because of the possible occupations which are accomplished as to produce the effect of enunciative completion. In this sense, this work analyses the linguistic constitution of the object, the enunciative conditions for the occupation of this place, as well as the effect that this occupation (or the lack of it) produces outside the sentence of organic structure.